Reformar el artículo 5 del libro ii- título V del derecho alimentos del Código de la Niñez y Adolescencia - Rivadeneira Mendoza, Napoleón Francisco de Asís (2015)
The Code of Children and Adolescents provides that grandparents are first obligated to pay alimony, if the principal can not provide and does not have the resources necessary to mime. This obligation to pay maintenance by grandparents, includes the senior, which breach their condition and their priority status not determined for these people several losses of such economic, social, affective and psychological. With the analysis in this research on the subject it can be inferred that the lack of clear regulations in regard to non-payment of child support, sanctions and consequences, creates instability within the operating field and one mistake with all the people who are engaged in the administration of justice, and that in view of the existing legal vacuum, place a series of extensive interpretations given, and of course everyone looks at his interests tending to deepen the problem raised. The fact that the obligor is detained indefinitely on account of non-payment of alimony does not guarantee in any way and under any circumstances, that being arrested will be able to fulfill that obligation, as there are people who often still at large have no work, or if they do they lose by neglect in days, here the question of how they will pay if they can not do, likewise in regard to the child or adolescent, emotionally grow and develop entirely full enjoyment of their rights , as stipulated in this law that protects him , knowing that because of it, either indirectly, the parent, the parent is deprived of his liberty , which is further evidence of the lack of consistency legal. However the detailed this particular, shall take into consideration the time it is being held without maintaining hope to get the amount to cover that debt, this research work tends to restore that attempted threat provision against the dignity of the obligors in the case before pointed out, since the pre-named rules are unconstitutional